O processo de construção do conhecimento sobre a situação de violência doméstica na perspectiva familiar e intergeracional a partir das narrativas de mulheres e de seus (ex-)parceiros - Holzmann, Eneida Regina Fabian (2018)
This research investigates the process of construction of the situation of domestic violence, between men and women, in the marital relationship. It is guided by the National Policy to Combat Violence Against Women, directed by Law nº 11.340/6, Law Maria da Penha, which required the creation of a network of diversified and interdisciplinary services in the areas of security and justice, social services and health, supported by the Unified Health System (SUS). Based on the systemic vision, it has as general objective to investigate in what way the family and intergenerational perspective contributes to the construction of knowledge with women in situation of domestic violence and with their (ex-)partners. It discusses the importance of the development, by public services, of forms of intervention that enable users to be accommodated by other men and women with similar experiences. It conducts a qualitative study and content analysis from the co-constructed narratives with eight heterosexual ex-couples, in a process of five individual and group interviews with each participant, including the co-construction of the ex-couple’s double genogram. It presents the perception of women and their (ex-)partners about the violence experienced in the marital relationship, the perception about the family/ intergenerational experiences involved in the construction of domestic violence, as well as the driving forces for the rescue of the identity and for exiting this situation, related to the family life cycle and the marriage life cycle. In the systemic perspective, the analysis focuses on the communication process of the ex-couple; the repetition of familiar patterns of communication, affectivity and familiar functioning regarding the construction of boundaries between the subsystems of the family; the presence of marital and family myths. The experience of psychological violence in the relation of the woman interviewed with her mother and the affective distancing between the man interviewed and his father are present, in a significant way, in the narratives co-constructed in the study. This experience of chronic psychological violence with the mother, for the women, had its continuity in the marital relationship, in which they experienced the same feelings of helplessness, of worthlessness, of abandonment. Men, in turn, also in a significant group, reported experiences of affective distancing and/or abandonment by the father, revealing a feeling of helplessness. In the construction of knowledge from the family and intergenerational perspective, through the sharing of individual experiences in the interviews in separate groups, women and men expressed that the rapprochement with family history contributed to self-knowledge, to the reaffirmation of their identity, their own value and the value of the family, in addition to enabling the opening for new meanings for the experience of marital violence. As a methodological result, the research brings the proposal for the rescue of history and family forces for women and men in situation of domestic violence, using a new instrument, the double genogram of the ex-couple, as a possible form of intervention for the public network